Clients’ Knowledge and Attitudes Toward Pre-Exposure Prophylaxis at Puskesmas Andalas, Makassar - Muhammad Arsyad Rahman; Muhammad Rachmat (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Pre-exposure prophylaxis (PrEP) is a highly effective strategy for preventing HIV, especially among high-risk groups such as injecting drug users, transgender individuals, sex workers, and men who have sex with men (MSM). In Indonesia, where HIV continues to pose a significant public health challenge, PrEP has the potential to decrease new infections. However, knowledge about PrEP among its users is limited. This study aims to investigate the relationship between users’ knowledge, attitudes, and adherence to PrEP, as well as their satisfaction with services, to design targeted interventions that address misconceptions, reduce stigma, and encourage long-term PrEP use. By offering insights into the experiences of PrEP users, the research seeks to improve PrEP accessibility, acceptability, and effectiveness, contributing to global efforts to end the HIV epidemic.Method: 200 registered PrEP clients in Puskesmas Andalas participated in this cross-sectional study. Structured questionnaires covering demographics, PrEP utilization, attitudes toward PrEP, and knowledge about PrEP were employed to gather data. The data were analyzed using descriptive statistics and chi-squared testing, considering p<0.05 as statistically significant.Result: The study results show that 56.5% of participants knew enough about PrEP, while 58.5% held favorable opinions about using it. However, attitudes (p=0.135) and knowledge (p=0.062) showed no discernible effects on PrEP use. The findings suggest that PrEP uptake may be more significantly influenced by factors such as accessibility, pricing, and social stigma, even though education and positive attitudes remain crucial. The study concludes that increasing PrEP utilization among high-risk populations requires comprehensive strategies that tackle these barriers.